2009
DOI: 10.1590/s1980-57642009dn30200004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mini-Mental State Examination scores according to different age and education strata, and sex, in a large Brazilian healthy sample

Abstract: Until better measures have been accepted for wider use, the Mini-Mental State Examination (MMSE) will continue to be utilized. In this context, knowledge on characteristics and determinants of its distribution for the Brazilian population are particularly valuable. The present study aimed to evaluate, based on multivariate analysis, the independent effect of age, educational level and sex, and their interactions, on MMSE scores in a healthy sample.MethodsDemographic data and scores on the MMSE of 1,553 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 41 publications
(33 reference statements)
3
30
0
6
Order By: Relevance
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
“…Scores on MMSE are greatly influenced by age and education level (13)(14)(15). Cognitive impairment and dementia have been associated with rural dwellers (16), increased rates of hospitalization (17,18), increased risk for falls (19,20), increased prevalence of fear of falling (21,22), diabetes mellitus (23,24), depression (17,25), and dependence in activities of daily living [ADL] (26).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] In the present study, we also found the ACE-R Verbal Fluency subscore to be dependent on both age and education. These effects have been reported in earlier research, with the greatest influence being education.…”
Section: Discussionsupporting
confidence: 77%
“…28,29 As mentioned, MMSE scores have also been significantly associated with age and education. 30 In their 2006 study, Mioshi et al 1 failed to find a significant interaction between age and performance on the ACE-R, possibly because of their small sample size (n = 63). However, Mathuranath et al 22 found a significant correlation between age and total scores on the original version (ACE) in their study of 488 healthy elderly people.…”
Section: Discussionmentioning
confidence: 97%
“…Previous Brazilian studies 26,27,28 indicated that older participants tend to have worse performance on cognitive tasks. For instance, Kochhann et al 29 studied 963 women aged between 20 and 92 years, in order to assess the independent effect and interactions between age, gender and education on the MMSE and noted that education and age influenced the MMSE scores. It is possible that in the present study no significant age differences were found due to the limited variability in the distribution of age.…”
Section: Discussionmentioning
confidence: 99%